Genetic diversity, population structure, and phylogeny of insular Spanish pepper landraces (Capsicum annuum L.) through phenotyping and genotyping-by-sequencing - Ortega-Albero, Neus; Barchi, Lorenzo; Fita, Ana; Díaz, Miguel; Martínez, Felipe; Luna-Prohens, Joana-Maria; Rodríguez-Burruezo, Adrián (Frontiers in Plant Science, 2024)
Pepper (Capsicum spp.) is one of the most important crops worldwide. Understanding the species' genetic background is key to preserve agrodiversity on-farm, to contribute to a more diverse and resilient agri-food sector, and to find new sources of variation that could be useful in future breeding programs. In this regard, varietal groups bred on insular environments have special interest as they have evolved quite isolated from continental forms, with a limited genetic exchange, mainly to unique genetic backgrounds. The present work explores the diversity of a plethora of Balearic landraces, corresponding to different local varietal types, through phenotyping and genotyping-by-sequencing (GBS). Mallorca and Eivissa landraces were phenotyped according to a comprehensive list of descriptors for plant, leaf, flower, fruit, pollen and seed, and were genotyped with Single Nucleotide Polymorphism (SNP) markers; population structure and their patterns of diversity were studied. The results showed a considerable morphological diversity for most traits analysed, within and between landraces. On the whole, in regard of genetic patterns, relatively low levels of heterozygosity and moderate genetic diversity for the studied landraces were found, although some of them exhibited diverse patterns. The materials were not grouped in specific clusters associated to each island, but mainly according to varietal types. These findings can serve as the basis for studying divergent evolutionary patterns associated with the corresponding populations. Finally, the results can contribute to further elucidation of genetic basis of Balearic landraces and serve as an inspiring case of study for other insular endemisms of cultivated species.